Analisis Faktor Risiko Kejadian Stunting Pada Balita Usia 24 – 59 Bulan Di Gurgur Pardomuan Kabupaten Aceh Tenggara - Mutiara Hikmah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Stunting incidents occur more frequently at the age of 24 – 59 months. Objective: This study aims to determine the risk factors for stunting in toddlers aged 24 - 59 months in Gurgur Pardomuan, Southeast Aceh Regency. Of the 372 babies measured, 84 were recorded as stunted. Method: This type of research is descriptive with a cross-sectional design. Data collection uses questionnaires and observations. The population in this study were all toddlers aged 24-59 months who had anthropometric measurements taken and the data were recorded at the Gurgur Pardomuan Community Health Center, Southeast Aceh Regency. The minimum sample is 74 people with a sample size ratio between cases and controls, namely 1: 1. Stunting is measured based on the score of height for age (TB/U). Toddler height data was measured using a microtome. Data on breastfeeding history, parents' education level, parents' income, and feeding patterns were collected using a questionnaire. Data on the history of low birth weight babies is collected based on the KIA book. Results: This study shows that there is a relationship between a history of exclusive breastfeeding and the incidence of stunting (p=0.017; or = 3.120), parental income (p=0.000; or = 6.481), history of low birth weight (p=0.041; or = 2,762). toddlers who do not receive exclusive breastfeeding have a 3,120 times risk of suffering from stunting compared to exclusively breastfed toddlers, low-income parents have a 6,481 times risk of suffering from stunting compared to high-income parents, LBW has a 2,762 times risk of suffering from stunting compared to those who do not. Conclusion: This research shows that exclusive breastfeeding, low parental income, and LBW are risk factors for stunting in toddlers aged 24 – 59 months.